Transient left bundle branch block in a young patient with a myocardial bridge: a case report - E. A. Novokhatskaya; A. S. Limonova; A. I. Ershova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Introduction. Transient complete left bundle branch block (LBBB) may occur against the background of various conditions, including coronary artery disease, cardiomyopathy of various origins, valvular diseases, heart rate abnormalities, acute pulmonary embolism, anesthesia, intrathoracic pressure changes, chest trauma, tumors, etc. Newly diagnosed complete LBBB in combination with the corresponding clinical manifestations is regarded as an acute coronary syndrome and requires immediate hospitalization.Results. A case of asymptomatic transient complete LBBB in a 36-yearold man without hemodynamically significant coronary atherosclerosis, with a myocardial bridge in the middle segment of left anterior descending artery with stenosis of 30%.Conclusion. Taking into account the paraclinical data, we studied the probability of transient complete LBBB against the background of left anterior descending artery myocardial bridging, as well as the probability of tachycardia-induced transient LBBB.